1978
DOI: 10.1126/science.96525
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Neoplasms of Genetic Origin in Drosophila melanogaster

Abstract: Malignant neoplasms that develop in 12 recessive-lethal, larval mutants of Drosophila melanogaster are discussed. These mutations affect the adult optic neuroblasts and ganglion-mother cells in the larval brain, the imaginal discs, and the hematopoietic organs. The malignant neoplasms exhibit fast, autonomous growth, loss of the capacity for differentiation, increased mobility and invasiveness, lethality in situ and after transplantation, and histological, fine structural, and karyotypic abnormalities. Interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
309
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(316 citation statements)
references
References 38 publications
4
309
0
Order By: Relevance
“…Drosophila Dlg is essential for prohibiting cell growth and for maintaining cell adhesion and cell polarity in both embryonic and adult tissues (Gateff 1978;Perrimon 1988;Bryant 1989, 1990;Woods et al 1996). In animals harboring dlg null mutations, aberrant cell polarity is revealed in the aberrant organization of both the actin and microtubule cytoskeletons, the transformation of columnar epithelial cells to a apolar morphology, and the delocalized distribution of cell adhesion molecules (Woods et al 1996).…”
mentioning
confidence: 99%
“…Drosophila Dlg is essential for prohibiting cell growth and for maintaining cell adhesion and cell polarity in both embryonic and adult tissues (Gateff 1978;Perrimon 1988;Bryant 1989, 1990;Woods et al 1996). In animals harboring dlg null mutations, aberrant cell polarity is revealed in the aberrant organization of both the actin and microtubule cytoskeletons, the transformation of columnar epithelial cells to a apolar morphology, and the delocalized distribution of cell adhesion molecules (Woods et al 1996).…”
mentioning
confidence: 99%
“…In Drosophila, the etiology of malignant and benign neoplasia due to recessive mutations in specific genes is firmly established (3,4 definitely in situ as well as after transplantation into wild-type hosts. The temperature-sensitive allele of the brain tumor mutant 1(3)mbt is in this respect especially instructive.…”
Section: Discussionmentioning
confidence: 99%
“…The four 1(2)tud alleles will be used to determine the molecular position of the gene in Southern blots. The most prominent phenotypic aberrations in the 1(1)d.lg-1 mutant are the tumorous imaginal discs and the highly enlarged brain hemispheres (3,10) (Table 1). The l(1)d.lg-1 gene region was reached via a genomic walk (11,12).…”
Section: Lethal (2) Tumorous Discsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudotumor formation generally occurs in two ways: there can be an overproliferation of hemocytes that begin to encapsulate healthy tissues, or there can be a disruption to the internal basement membrane (such as by an actual tumor) that activates a wild-type encapsulation response. 19 Jose Pastor-Pareja (Tian Xu's lab, Yale University) is using flies double mutant in the Ras and scribble genes, which exhibit tumor growth similar to human metastatic cancers, to dissect the fly immune response against malignant fly tumors. Specifically, he found that plasmatocytes adhere to the surface of tumors and can restrict tumor growth, and that tumors induce the JAK-STAT pathway and stimulate greater proliferation of hemocytes.…”
Section: Cellular Immunitymentioning
confidence: 99%